MENINGKATKAN SUMBER DAYA MANUSIA DESA CIPURUT DALAM MENYONGSONG ERA TEKNOLOGI 4.0 - CSA Teddy Lesmana; Rika Rahmawati; Saepul Manan; Mohamad Salman Farizi; Egit Pudarwati; ami apriatna; Ferry Rajib Pamungkas; Adrian Agis S.L; Nanda Rizki Amalia; Nauval aziz; Ripki Mohamad Sopian; Muh Reza Multiaha; Aqil Rivaldi; Husnul Sabila; Rudi Hermawan; Eva Elis; Putri Ulil Fatma Aulia; Anita Rahayu; Panca Adhi Darmawan; Redi Supardi; Agung Pratama; Ardi Julianto; Luni Anggraeni; Ade Solihin Sopandi; Jamaludin; Ikram Mulkarim; Muhammad Satrio Kamal.; Yusuf Muharom; Sri Ayu Maharani; Rizal A Ardiyansyah; Siti Aisyah; Fatimah Maolida Maolida Salsabilla; Egi Suherman; Nurul Yulia Fatma (Jurnal Abdi Nusa, 2021)
To welcome the era of technology 4.0, and there are still many human resources who do not understand how to apply the technology that is currently developing, it is necessary to have socialization and training in the Cipurut Village environment. With the current condition which is still in the covid-19 pandemic, almost all activities use the internet, such as education and services to the community. With the development of the digital world today, many things, especially those related to educational activities and services to the community, can use the digital system, making it easier and more practical. With many people, especially human resources at the Cipurut village office, who do not yet understand digital technology, it is necessary to have the training and workshops to improve the competence of human resources.As a result of the current use of technology, the existing community can already use it to help their activities, such as online sales, public services, etc. For village officials themselves, they can use digital technology to assist in providing services to the community.